Implementasi Sensor VOC Digital pada Sistem Monitoring dan Pengendalian Asap Rokok dalam Ruangan Berbasis Internet of Things - Muhammad Arif Hidayatullah; Abdul Azis; Perawati Perawati (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
Cigarette smoke is one of the sources of indoor air pollution that contains various harmful compounds, including Volatile Organic Compounds (VOC), which can reduce indoor air quality and negatively affect human health. This study aims to design and develop an indoor cigarette smoke control system based on the MiCS-5524 VOC sensor and Internet of Things (IoT) technology with monitoring through Telegram on an Android device. The proposed system uses an Arduino Uno as the main controller integrated with an ESP8266 module, MiCS-5524 VOC sensor, L298N motor driver, DC fan, activated carbon filter, buzzer, and 16×2 I2C LCD. The test results show that the MiCS-5524 sensor is capable of detecting changes in VOC concentration caused by cigarette smoke exposure, while the system automatically activates the fan and buzzer according to the detected air quality conditions. The ESP8266 module successfully transmits monitoring data to Telegram Android in real-time with an average transmission time of 2.3 seconds. Furthermore, the activated carbon filter contributes to reducing VOC levels, resulting in improved indoor air quality. The results indicate that the developed system is capable of performing automatic detection, control, and monitoring of indoor air quality.